Understanding the impact of acne vulgaris and associated psychological distress on self-esteem and quality of life via regression modeling with CADI, DLQI, and WHOQoL - A. S. M. Morshed; Towhida Noor; Md Ashraf Uddin Ahmed; Fahmida Sultana Mili; Shuma Ikram; Mashiqur Rahman; Shamim Ahmed; Mohammad Borhan Uddin (Scientific Reports, 2023)
Abstract Acne vulgaris (AV) is a psychosomatic disorder and can negatively affect individuals, especially in terms of psychological well-being, self-esteem, and quality of life (QoL). The current study aimed to investigate the association between AV and psychological health, as well as the influence of acne and psychological distress in predicting patients' self-esteem and QoL. This cross-sectional study included 150 patients clinically diagnosed with AV. The severity of acne was measured using GAGS, and following that, patients were instructed to complete the following forms: DASS-21, RSES, CADI, DLQI, and WHOQoL. Female AV patients had significantly higher depression (p = 0.003, t = 3.025) and anxiety (p < 0.001, t = 3.683). Pearson's correlation analysis indicated a strong, positive, and significant correlation between having acne and experiencing depression (r = 0.630), anxiety (r = 0.661), and stress (r = 0.758) (p < 0.001). Multiple regression analysis suggested acne and associated psychological distress had a significant and negative impact on the patient's self-esteem and quality of life. This study highlights the multifaceted consequences of AV and the need to manage its psychological distress. It emphasizes the need for holistic patient care that addresses acne's physical and emotional aspects, with the ultimate goal of enhancing well-being and QoL.